METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF ASCORBIC ACID AND FOLIC ACID VITAMINS BY REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD IN CYANOBACTERIAL METABOLITES AND NUTRACEUTICAL FORMULATION - Ss, Kachhawah; B, Biswal; Jain, Anurekha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: It was aimed to estimate ascorbic acid (ASC) and folic acid (FLC) in cyanobacterial metabolite by the reverse-phase high-performance liquid chromatography (RP-HPLC) method, and the work was also extended to nutraceutical formulation. Methods: RP-HPLC method were developed for simultaneous estimation of two vitamins ASC and FLC in cyanobacterial metabolite and nutraceutical using isosbestic point at wavelength 280 nm. Method was selected after calculating system suitability and validated as per ICH guidelines. Results: The developed analytical method parameters found within limits prescribed by ICH and USP guidelines. The retention time was found to be 2.334 and 3.892, respectively, for ASC and FLC. Limit of detection and limit of quantification for ASC and FLC were found to be 0.087 and 0.263 Âµg/ml, 0.052 and 0.159 Âµg/ml, respectively. Recovery studies show that method is capable of recovering analytes from its formulation. The method is meeting the criteria for validation as per the guidelines. Conclusion: The method is simple, precise, specific, and accurate. The newly developed method can be used in pharmaceutical industry for routine analysis of ASC and FLC in tablet dosage form. Keywords: Cyanobacteria, Nutraceutical, Reverse-phase high-performance liquid chromatography, Ascorbic acid, Folic acid, Vitamins, Metabolites.